2019
DOI: 10.1001/jama.2019.2021
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Year of Birth and 1-Year Survival Among Extremely Preterm Infants in Sweden During 2004-2007 and 2014-2016

Abstract: Since 2004Since -2007, national guidelines and recommendations have been developed for the management of extremely preterm births in Sweden. If and how more uniform management has affected infant survival is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
138
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 224 publications
(152 citation statements)
references
References 42 publications
7
138
1
6
Order By: Relevance
“…Over 90% of fetuses in our cohort were admitted to NICU, and three quarters of the total population survived to discharge. This is in keeping with results from Sweden 28 , 29 and Japan 30 , 31 although of course our numbers are smaller and confidence intervals therefore wider. In England, the EPICure studies demonstrated increased admissions to NICU between 1995 and 2006 1 , probably linked to an increase in the numbers of babies born at these gestations as well as to changes in attitudes in the delivery room 32 .…”
Section: Discussionsupporting
confidence: 90%
“…Over 90% of fetuses in our cohort were admitted to NICU, and three quarters of the total population survived to discharge. This is in keeping with results from Sweden 28 , 29 and Japan 30 , 31 although of course our numbers are smaller and confidence intervals therefore wider. In England, the EPICure studies demonstrated increased admissions to NICU between 1995 and 2006 1 , probably linked to an increase in the numbers of babies born at these gestations as well as to changes in attitudes in the delivery room 32 .…”
Section: Discussionsupporting
confidence: 90%
“…At baseline, Sweden provides healthcare at minimal cost to all inhabitants including mental health services (39,40). Moreover, Sweden is among the countries with the lowest rates of preterm births (between 5-6%) (41), likely due to the economic stability of the country and the focus of the government on perinatal health, as well as on the timely and adequate access to healthcare services (42). Despite the fact that the Swedish COVID-19 strategy did not include a general lockdown, but was instead based on voluntary social distancing guidelines (16), we still find a clear association of theCOVID-19 pandemic with the mental health of pregnant women.…”
Section: Previous Literaturementioning
confidence: 99%
“…As survival rates following preterm birth increase with medical advances, more becomes known about the developmental outcomes of children born preterm ( 7 ). Children are considered preterm if they were born prior to or during the thirty-sixth week of gestation and full-term if they were born between the thirty-seventh and forty-second weeks of gestation ( 8 ).…”
Section: Introductionmentioning
confidence: 99%